Preference of Methods and Media for Promotion of Drug Abuse Prevention According to the Point of View of Students and Parents in Bima - Ade Wulandari; Nani Nurhaeni; Martiningsih Martiningsih; Ahmad Ahmad (Universitas Airlangga, 2022)
Background: Drug abuse in the Bima region increases from year to year, and it is dominated by students. In 2017 there were 44 cases handled, increased to 79 cases in 2018, and 71 cases in 2019. Bima region as a port city that connects Sumbawa island with a number of large islands in Indonesia has become a risk factor for illicit drug trafficking. Socialization on the dangers of drug abuse that has been carried out in the school environment has a number of limitations, especially in terms of time, methods, and media as well as the number of target audiences that are covered by the activity. It is necessary to develop a method and media approach that is appropriate to the developmental characteristics of adolescents. Objectives: This study aims to obtain an overview of the need for methods and media for the promotion of drug abuse prevention from the point of view of students and parents in Bima. Methods: This research was conducted through a survey method. It was carried out in six Junior High Schools (SMP) in Bima from May to October 2021. Research variables consisted of demographic characteristics; the history of drug and substance use by students; and the need for prevention of drug abuse based on methods, media, locations, frequency, and information providers in Bima. Research data were collected using a questionnaire instrument. Population of this research was students and their parents. The sample size was determined based on the Slovin formula. Data were obtained from 275 students and 70 students' parents. Research data analysis was done with univariate statistics. Results: Students and parents need drug abuse prevention promotion activities that are implemented by health workers either directly or through audiovisual media and social media, such as film screenings on television and gadgets. The promotion is conducted on a scheduled 2-3 times a year. Most of the respondents chose the school and house for the promotion activities. Conclusion: Students and parents had the same interests and opinions about the need for methods and media to promote drug abuse prevention. The results of this research are expected to be a recommendation for the development of a promotion program for the prevention of adolescent drug abuse in Bima.